Djibouti : Selected Issues. (IMF Staff Country Reports; Country Report, 2004)
The most important challenge faced by the Djibouti authorities is to achieve high rates of economic growth in order to create employment opportunities for a rapidly increasing labor force and to alleviate rising poverty. In this paper, developments and the role of the financial system during the program period are reviewed. Then, the currency board arrangement (CBA) and its role in macroeconomic developments are discussed. The study also discusses the main financial sector reforms and explains why their impact has been limited.